Recensiones - S. de Anitua,; Mantilla, Sebastián; S. M.,; Montes, Santiago; I. C.,; I. M. B.,; Casín, Isabel (ECA: Estudios Centroamericanos, 1971)
No hay resúmenes disponibles.ECA Estudios Centroamericanos, Vol. 26, No. 272, 1971: 356-368.